English teaching and learning in three primary schools in Iceland : the perspective of immigrant students - Karl Sigtryggsson 1984- (2015)
This is a study conducted on the perspective of 17 immigrant students aged 13-16 towards their English learning and teaching in Icelandic compulsory schools and on what future aspirations they have for their English. The significance of the study is twofold: to inspire my own professional development as an English teacher working in culturally diverse classrooms, and to give voice to a group of students in a research context that builds on existing international and national research whilst contributing fresh insights. This is a qualitative study that draws on the methods of narrative inquiry to conduct three focus group interviews in three different schools in Iceland. The students came from nine different countries and had been living in Iceland for 2-15 years. They were asked about their lessons, what they liked, what they thought could be improved, or what was missing, and about their future aspirations. The findings suggest that students seek more diversity in teaching methods, which they describe as predominantly focused on text- and workbook. Student responses further indicate the need for more meaningful learning approaches with emphasis on practical language usage. While some students felt that English was necessary and would serve them in their future endeavors to study or work abroad, others felt that it was not relevant to their future lives. English is a core curricular subject in Iceland, in recognition of its academic and social value. Therefore, teachers need to not only make their practice more meaningful to respond to academic and social needs, but to do this in a way that responds to the diverse cultural reality of students. These findings are intended to inform my own professional development as an effective English language teacher in an increasingly multicultural society. Þessi rannsókn fjallar um viðhorf 17 innfluttra (immigrant) nemenda á aldrinum 13-16 ára, til enskunáms og -kennslu í íslenskum grunnskólum, og hvaða væntingar þeir hafa til ensku í tengslum við framtíð sína. Gildi ...